NEW VC ASPIRES TO LEAD USM IN ENSURING THE SUCCESS OF PPPM (PT) AND THE APEX AGENDA - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
USM, PENANG, 4 October 2016 – The newly appointed ViceChancellor of Universiti Sains Malaysia (USM), Professor Datuk Dr. Asma Ismail is steadfast in ensuring that USM would be able to implement the Malaysia Education Blueprint 2015 – 2025 (Higher Education) or PPPM (PT) and the Accelerated Programme for Excellence (APEX) agenda by providing the whole campus community with an understanding of the aspiration.